Nivel de ventas en los negocios de Cheese and Cheese de la ciudad de Babahoyo - Guzman Zapata, Leonardo Flavio (2018)
CHEESE AND CHEES is an enterprise that was born on December 1, 2007 in the city of Babahoyo with a capital of $ 4,900, investment for the construction of the "cart" and supplies, this business activity is dedicated to the sale of hamburgers, Hot Dogs and Tacos; and, it is a response to the lack of work sources, this micro business is located from the beginning next to the parking lot of AKI Stores in this city. This site is chosen, as it is the place where a great human mobility activity exists at that time, because on this site public vehicles are expected to move to the towns of Ventanas, Quevedo, Vinces, Mocache, Puebloviejo, San Juan, Isla de Bejucal, Caluma, Catarama, Ricaurte, Baba, Pimocha and other towns.